Implementasi Electronic Health Record di RSUD Loekmono Hadi Kudus - Ahmad Farid; Fadhila Nazwa Rahmania (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
This study explores the implementation process of the Electronic Health Record (EHR) system at RSUD Loekmono Hadi Kudus. The objective is to gain an in-depth understanding of the implementation phases, identify encountered challenges, and assess the system’s impact on the efficiency of medical record management and quality of healthcare services. A qualitative methodology was employed, using in-depth interviews and direct field observations for data collection. The findings indicate that the EHR system facilitates easier access to patient data, accelerates service delivery, and improves the accuracy and reliability of medical information. Despite facing several challenges related to technical issues and human resources, training and adaptation efforts proved effective in overcoming these obstacles. The study recommends ongoing system enhancements and continuous training for staff to ensure more effective utilization of EHR in the future.